Studies on Persistence of Ready-mix Chlorpyrifos+Cypermethrin Formulation on Tomato (Solanum lycopersicum L.) - Banshtu, Tanuja; Kumar Patyal, Surender; Singh Chandel, Rajeshwar (International Journal of Bio-resource and Stress Management, 2023)
Persistence of ready-mix and individual insecticide chlorpyrifos and cypermethrin was studied during 2009 and 2010 under field conditions. Chlorpyrifos and cypermethrin were applied at recommended rate 500 and 50 g ai ha-1 and at double the recommended rate on tomato crop. The fruits and soil samples were collected after second spray at different intervals. Residues were extracted with acetone and cleaned up by column chromatography. Residues of both insecticides were determined by using gas chromatograph, Agilent 6890N having electron capture detector. In fruits, the residues of chlorpyrifos and cypermethrin reached below the limit of determination in 10 and 7 days at recommended rate and in 15 and 10 days at double recommended rate, respectively. In ready-mix product, chlorpyrifos deposits reduced to half in 1.24-1.42 days and cypermethrin deposits required 1.38-1.73 days to reduce to half but when applied individually, chlorpyrifos initial deposits were reduced to their half in 1.07-1.39 days and cypermethrin deposits became half in 1.57-2.08 days. In soil, residues of chlorpyrifos persisted upto10 days in individual as well as in ready-mix insecticides. However, residues of cypermethrin were below determination limit in 10th day sampling in case of individual application of insecticides whereas, cypermethrin residues were not detected even on the 0 day sampled soil in ready-mix formulation. The study revealed that the persistence behavior in fruits were almost same when applied individually or as ready-mix.